Anarchism and non-domination. Issue 3 (2nd September 2019) - Kinna, Ruth; Prichard, Alex
ABSTRACT: In this article we recover the classical anarchist deployment of republican tropes of non-domination, tyranny and slavery, to expose the conservative limits of the contemporary neo-Roman republican revival. For the anarchists, the modern nation state and the institution of private property are antithetical to freedom as non-domination, acting as structural constraints to freedom rather than the means for its realisation. We re-examine the grounds of this critique to advance two arguments. First, that a commitment to either the state or private property represents an unwarranted positive moral and ethical commitment that skews the negative theory of freedom contemporary republicans seek to develop. Second, the prior moral commitment to the state renders neo-Roman republicanism fundamentally conservative. Anarchist theories of freedom as non-domination push much further than the contemporary republican revival seems to permit, opening new possibilities for institutional and constitutional innovation while remaining consistent with the core republican normative value of non-domination.